PENERAPAN TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP NYERI AKUT PADA PASIEN POST AMPUTATION ABOVE KNEE DENGAN DIAGNOSA OSTEOMYELITIS TIBIA FIBULA DEXTRA - Gantri Septiani; Tuti Pahria; Sri Hartati Pratiwi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Osteomyelitis is a bone infection that can cause extensive tissue damage, potentially leading to amputation. Post-amputation patients commonly experience acute pain influenced by inflammatory processes, surgical trauma, and peripheral nerve stimulation. Pharmacological approaches are often used, but non-pharmacological therapies such as Spiritual Emotional Freedom Technique (SEFT) are considered to have the potential to help reduce pain perception thru relaxation and emotional regulation mechanisms. This study was conducted to examine the effectiveness of SEFT on post-amputation patients due to osteomyelitis. This study uses a case report design on a 63-year-old male patient diagnosed with right tibia-fibula osteomyelitis post-amputation. The SEFT intervention was administered over four sessions, each lasting 15 minutes. Pain evaluation was performed using the Numeric Rating Scale (NRS) before and after the intervention. After four SEFT sessions, the pain intensity decreased from a scale of 7 to 4. In addition to pain reduction, patients reported increased relaxation, emotional calmness, and improved sleep quality. Vital signs, particularly heart rate, indicate improvement toward the normal range. This finding suggests that SEFT is effective as a complementary intervention for reducing acute pain in post-amputation patients. The combination of meridian point stimulation and spiritual affirmations is believed to contribute to physiological relaxation and increased self-acceptance. This intervention has the potential to be applied in nursing practice as a safe, simple, and side-effect-free holistic approach.